MiR-452 Regulates C2C12 Myoblast Proliferation and Differentiation via Targeting ANGPT1 - Yang, Lingzhi; Qi, Qi; Wang, Jian; Song, Chengchuang; Wang, Yanhong; Chen, Xi; Chen, Hong; Zhang, Chunlei; Hu, Linyong; Fang, Xingtang (Frontiers in Genetics, 2021)
microRNAs are a kind of endogenous, non-coding, single-strand small RNA. They have been reported as an important regulatory factor in skeletal myogenesis. In this study, miR-452 was selected from RNA high-throughput sequencing data to explore its regulatory role in myogenesis. Functionally, overexpression of miR-452 could promote C2C12 myoblasts proliferation, whereas inhibit their differentiation. On the contrary, inhibition of miR-452 could impede C2C12 myoblasts proliferation, but enhance their differentiation. Bioinformatics software prediction and dual luciferase report analysis experiments showed that ANGPT1, RB1 and CACNB4 were the potential target genes of miR-452. To further confirm the target relationship between ANGPT1, RB1, and CACNB4 with miR-452, the mRNA level and protein level of these genes were detected by using RT-qPCR and western blot, respectively. Results analysis indicated that ANGPT1 was a target gene of miR-452. In addition, knockdown of ANGPT1 could obviously promote C2C12 myoblasts proliferation but block their differentiation. In summary, these results demonstrated that miR-452 promoted C2C12 myoblasts proliferation and inhibited their differentiation via targeting ANGPT1.